Education on Revenue Increase Strategies and Business Sustainability through Digital-Based Promotion, Management Strengthening, and Business Innovation - Nur Zaeni; Abdullah Ade Suryobuwono (Siber Nusantara of Community Service Review, 2026)
This community service activity aims to increase the income and business sustainability of micro and small businesses through the implementation of digital-based promotional strategies, strengthening business management, and product and service innovation. The main problems faced by partners include limited use of digital technology, weak financial and operational management, and a lack of product differentiation in the market. The implementation method includes training, mentoring, and periodic evaluations focused on optimizing social media, marketplaces, and the use of simple digital tools for marketing. In addition, managerial capacity is strengthened through the preparation of simple bookkeeping, business planning, and quality control. Business innovation is developed through product diversification, increasing added value, and adapting to market needs. The results of the activity show an increase in partners' understanding and skills in digital marketing, improvements to business management systems, and increased product competitiveness. The resulting impact is seen in an increase in the number of customers, expansion of market reach, and an increase in business turnover. Thus, this integrated strategy has proven effective in driving revenue growth while maintaining sustainable business sustainability in the digital economy era.